Diabetes prevalence and socioeconomic status: a population based study showing increased prevalence of type 2 diabetes mellitus in deprived areas. Issue 3 (1st March 2000) - Connolly, V; Unwin, N; Sherriff, P; Bilous, R; Kelly, W
Abstract : OBJECTIVE: To establish the relation between socioeconomic status and the age-sex specific prevalence of type 1 and type 2 diabetes mellitus. The hypothesis was that prevalence of type 2 diabetes would be inversely related to socioeconomic status but there would be no association with the prevalence of type 1 diabetes and socioeconomic status. SETTING: Middlesbrough and East Cleveland, United Kingdom, district population 287 157. PATIENTS: 4313 persons with diabetes identified from primary care and hospital records. RESULTS: The overall age adjusted prevalence was 15.60 per 1000 population. There was a significant trend between the prevalence of type 2 diabetes and quintile of deprivation score in men and women (χ 2 for linear trend, p<0.001). In men the prevalence in the least deprived quintile was 13.4 per 1000 (95% confidence intervals (95% CI) 11.44, 15.36) compared with 17.22 per 1000 (95% CI 15.51, 18.92) in the most deprived. For women the prevalence was 10.84 per 1000 (95% CI 9.00, 12.69) compared with 15.48 per 1000 (95% CI 13.84, 17.11) in the most deprived. The increased prevalence of diabetes in the most deprived areas was accounted for by increased prevalence of type 2 diabetes in the age band 40–69 years. There was no association between the prevalence of type 1 diabetes and socioeconomic status. CONCLUSION: These data confirm an inverse association between socioeconomic status and the prevalence of type 2 diabetes in the middle years of life. This finding suggests that exposure to factors that are implicated in the causation of diabetes is more common in deprived areas.